Rare Coexistence of Inv(16) and T(9;22) in Patient with Chronic Myeloid Leukaemia Presenting as Blast Crisis - Abbas, Aymen; Kalas, Mutaz; Raidullah, Emadullah (International Journal of Innovative Research in Medical Science, 2023)
Chronic myeloid leukemia (CML) is associated with BCR-ABL1 fusion gene located on chromosome 22 as a result of a t(9;22)(q34;q11.2) translocation in about 90% of the patients. Also, coexistence of the t(9;22) and inv(16) chromosomal aberrations is a rare occurrence that has been described in CML (mainly the myeloid blast phase [CML-BP]), de novo AML, and a few cases of therapy-related AML (t-AML). We describe a 22 years old male in primary blast crisis of CML as initial presentation with coexistence of the t(9;22) and inv(16). Majority of cases, in which these abnormalities coexist are CML-BP, which is typically characterized by an aggressive clinical course rapid disease progression and resistance to chemotherapy.